الاستفادة من الطاقة الحرارية المفقودة مع دسع مراجل محطة توليد بانياس - أيوب حسن; عهد سليمان; رامز مصطفى (Tishreen University, 2019)
تستخدم جميع الصناعات المراجل (مولدات البخار) لاحتياجات الطاقة لديها، ويستخدم البخار إما بشكل مباشر، أو عبر مبادلات أو أوعية ضغط. تحتوي المياه الخام المستخدمة في هذه المراجل تراكيز مختلفة من الشوائب التي يمكن التخلص منها من خلال المعالجة الأولية، كالتصفية عبر الفلاتر، وإزالة القساوه وبعض الأملاح أما الشوائب المتبقية في بعض الحالات فتتجمع ويزداد تركيزها داخل  المراجل عند عملها المستمر. إن زيادة التراكيز يؤدي إلى تشكل الحمأه والشوائب في أنابيب المرجل والتي تذهب مع البخار الحي . وبالتالي لا بد من صرف جزء من  المياه  لأنه  يؤدي إلى تخفيض هذه الشوائب المتراكمة، مع مراعاة عدم زيادة كمية الدسع  لأن ذلك سيؤدي إلى زيادة كمية مياه التعويض، وبالتالي زيادة المعالجة الكيميائية والوقود. ويستخدم دسع المراجل من أجل حمايتها و المحافظة على سلامتها, من خلال  الدسع السطحي الذي  يستخدم لإنقاص المواد الصلبة الذائبة التي تشكل الشوائب (القشور)، والدسع من أسفل المراجل(أسفل الحلة) لإزالة الرواسب (الصلبة غير الذائبة) التي تتجمع في أسفلها. ويمكن تقليل  فاقد الطاقة الناجم عن الدسع من خلال استرجاع الحرارة منه، وكذلك استخدام الدسع الآلي. Many industries use boilers to generate steam for their energy needs. The steam may be used directly In the process or indirectly via heat exchangers or steam jacketed vessels. The raw water used to feed these boilers contains varying levels of impurities that are removed by pre-treatment such as filtration, softening and demineralization. The remaining impurities, although small in some cases, remain in the boiler accumulating in higher and higher concentrations as the operation continues. These increasing concentrations lead to the formation of sludge, scaling of the boiler tubes and carry-over of solids in the process steam. Blowing down some of the water in the steam drum to the drain reduces the level of these accumulated impurities. Care must be taken to avoid excessive blowdown, as this would increase the demand for make-up (feed) water, treatment chemicals, and fuel. Blowdown of the boiler water is done to protect the integrity of the boiler by  using a "surface" blowdown to reduce the level of dissolved solids that can form scales , and "bottom" blowdown which reduces the quantity of un dissolved solids (sludge) which collect in the lower parts of the boiler (mud drum). To reduce the blowdown heat losses, heat recovery and automatic blowdown can be used.